2015
DOI: 10.1007/s11523-015-0370-0
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Inhibitor Valproic Acid Sensitizes Gemcitabine-Induced Cytotoxicity in Gemcitabine-Resistant Pancreatic Cancer Cells Possibly Through Inhibition of the DNA Repair Protein Gamma-H2AX

Abstract: These results indicate that VPA enhances GEM-induced cytotoxicity in GEM-resistant pancreatic cancer cells, possibly through inhibition of DNA damage signaling and repair. Our study suggests VPA as a potential therapeutic agent for combinatorial treatment with GEM in pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…There is also evidence that elevating histone H3 acetylation may sensitize cancer cells to chemotherapeutics [25,26]. VPA promotes cisplatin sensitivity [27] and restores erlotinib [28], sorafenib [29], gemcitabine, and vincristine responsiveness [30,31]. Recent investigations demonstrate that VPA may also act on temsirolimus-resistant bladder cancer [13] and everolimus-resistant renal cell carcinoma cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that elevating histone H3 acetylation may sensitize cancer cells to chemotherapeutics [25,26]. VPA promotes cisplatin sensitivity [27] and restores erlotinib [28], sorafenib [29], gemcitabine, and vincristine responsiveness [30,31]. Recent investigations demonstrate that VPA may also act on temsirolimus-resistant bladder cancer [13] and everolimus-resistant renal cell carcinoma cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…Valproic acid was shown to enhance the cytotoxic effect on gynecologic cancer cells in combination with an aurora kinase inhibitor [40]. Valproic acid was also reported to sensitize gemcitabine-induced cytotoxicity in gemcitabine-resistant pancreatic cancer cells [41].…”
Section: Resultsmentioning
confidence: 99%
“…An evaluation of the histone acetylation status revealed increased aH3 and aH4 expression in the resistant and sensitive cells, suggesting an epigenetic mechanism [ 63 ]. Recent investigations have shown that VPA also promotes cisplatin sensitivity [ 64 ] and restores erlotinib [ 65 ], sorafenib [ 66 ], gemcitabine, and vincristine responsiveness [ 67 , 68 ]. However, the specific molecular mechanisms need to be verified in future research.…”
Section: Application Of the Epigenetic Effect Of Antiepileptic Drugsmentioning
confidence: 99%